Analysis of workability, mechanical strength and durability by the FT-IR method of concrete based on silica-limestone sand preserved in aggressive environments - Hima Abdelkader; Tarek Djedid; Mohammed Mani; Abdelhamid Guettala (Fracture and Structural Integrity)
The interest of using combined sand of equal percentage of silica and limestone becomes evident in the formulation of compacted concrete in several previous works around the world, due to the formidable percentage of fines that improves the compactness and increases various mechanical resistances, which produces a more durable construction against different probable aggressions.